Search for neutral supersymmetric Higgs Bosons in multijet events at sqrt[s]=1.96 TeV. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2005)
We have performed a search for neutral Higgs bosons produced in association with bottom quarks in pp collisions, using 260 pb-1 of data collected with the D0 detector in Run II of the Fermilab Tevatron Collider. The cross sections for these processes are enhanced in many extensions of the standard model (SM), such as in its minimal supersymmetric extension at large tanbeta. The results of our analysis agree with expectations from the SM, and we use our measurements to set upper limits on the production of neutral Higgs bosons in the mass range of 90 to 150 GeV.